PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH DALAM MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATERI POKOK GERAK LURUS KELAS X SMA NEGERI 3 TANJUNG BALAI T.P 2014 / 2015 - Khadijah Nasution; Juniar Hutahaean (UNIVERSITAS NEGERI MEDAN, 2015)
This study aims to determine the effect of the application of problem-based learning model to activities and student learning outcomes in a straight motion of matter in class X in SMAN 3 Tanjungbalai TP 2014/2015. This research is quasi experiment. The population in this study were all students of class X semester 3 Tanjungbalai SMA consists of five classes. The study sample was taken two classes, namely class X MIA-1 (as an experimental class) and Class X MIA-3 (as a control class), each of which amounted to 30 students as determined by cluster random sampling. Then given a different treatment, the experimental class with a problem-based learning model and grade control with conventional learning. The data used in this study used an essay test were 10 items that have been divalidkan by the validator. The results were obtained average values pretest experimental class was 18.2 and the average value of the control class is 18.37. After completion of the post-test study with an average yield of 75.83 experimental class and control class 70.3. Activities and student learning outcomes in a straight motion of matter by applying problem-based learning model is better than the conventional learning in class X SMA semester 3 Tanjungbalai TP 2014/2015.Keywords : Problem Based Learning, Conventional, Learning Activities, Learning Outcome